Critical Discourse Analysis of Suara.Com's News Regarding Student Deaths During Campus Training - Nindy Advianturi; Muhammad Rais Almajid; Murakami, Kazushige (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2024)
Text in written discourse is one of the intermediaries in conveying information to readers. Discourse in critical discourse analysis studies can include microstructural, mesostructural, and macrostructural aspects. This study aims to identify microstructural, mesostructural, and macrostructural aspects in Suara.com news texts regarding the deaths of students from Sebelas Maret University Surakarta and Hasanuddin University Makassar during the Training Menwa and Mapala which occurred in November 2021 and January 2023, as well as members of the Nature Lovers Community (KPA) outside the campus. The object of this study is a news text entitled ‘Kasus yang Selalu Terulang Kembali, Deretan Kasus Mahasiswa Meninggal Saat Diksar Kampus’ which was released by Suara.com on January 18, 2023. The object of the study was studied using Norman Fairclough's critical discourse analysis approach which includes microstructural, mesostructural, and macrostructural aspects. Qualitative descriptive is used as a method in this study. Data collection was carried out by listening, recording and taking screenshots of words or sentences in Suara.com news containing discourse based on microstructural, mesostructural and macrostructural aspects. Data analysis was carried out by collecting, reducing, presenting data, and ending with drawing conclusions. The results of the analysis found that in the microstructural aspect Suara.com produced news texts through the use of diction, the arrangement of cause-effect sentences, and the acquisition of sources in direct quotations. In the mesostructural aspect, the realization of the text displayed by Suara.com also reflects Suara.com's vision, namely honest, balanced and independent news. Meanwhile, in the macrostructural aspect, it was found that the motivation in presenting news texts was that readers were led to give positive appreciation to Suara.com as one of the popular media in reporting cases for the purpose of justice.